2012
DOI: 10.1262/jrd.2012-043
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Apoptotic Status in the Bovine Placentome between Spontaneous and Induced Parturition

Abstract: Abstract.We conducted this study to analyze apoptotic changes in the bovine placentome at spontaneous and induced parturition. Cows delivered i) after the administration of dexamethasone followed by prostaglandin F 2α and estriol, ii) after the administration of prostaglandin F 2α and estriol or iii) spontaneously. Prepartum changes in plasma progesterone and estradiol-17β concentrations were similar between spontaneous and induced parturition. Messenger RNA of BCL2-related protein A1 (BCL2A1), an antiapoptoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 34 publications
2
10
1
2
Order By: Relevance
“…These results are in agreement with another study describing a decline in the proliferation and an increase in cell death in maternal crypt epithelium, maternal stroma, and fetal chorionic epithelium during pregnancy and near parturition as physiological processes. 9 The same processes were observed by other authors 23 : they described the regulation of cell proliferation and regression as key for placental maturation during late pregnancy and for detachment of the fetal membrane in the early postpartum period. It was mentioned in another study that increased apoptosis is involved in placental maturation, 19 and similar results were found in the placentome of yaks.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…These results are in agreement with another study describing a decline in the proliferation and an increase in cell death in maternal crypt epithelium, maternal stroma, and fetal chorionic epithelium during pregnancy and near parturition as physiological processes. 9 The same processes were observed by other authors 23 : they described the regulation of cell proliferation and regression as key for placental maturation during late pregnancy and for detachment of the fetal membrane in the early postpartum period. It was mentioned in another study that increased apoptosis is involved in placental maturation, 19 and similar results were found in the placentome of yaks.…”
Section: Discussionsupporting
confidence: 70%
“…This was followed by a semiquantitative analysis of these parameters by evaluation of the whole section. Cellular debris, inflammation, and mineralization were classified as mild (þ,n¼ 1-10 foci per section), moderate (þþ,n¼ [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], and severe (þþþ,n¼ >30). Vasculitis was classified as mild (þ,n¼ 1-6), moderate (þþ,n¼ 7-12), and severe (þþþ,n¼ > 12).…”
Section: Histologic Examinationmentioning
confidence: 99%
“…It has been shown that cows are at greater risk of retained foetal membranes following medical induction of parturition with an incidence of 19-53% (Lewing et al, 1985;Bo et al, 1992;Hirayama et al, 2012). There are inconsistent reports about this phenomenon in sheep.…”
Section: Discussionmentioning
confidence: 99%
“…54 Placental apoptosis related to parturition has also been observed in non-human placental tissues. Hirayama et al 55 observed that apoptotic cells in bovine placentomes increase as pregnancy progresses, peaking at the time of parturition. These apoptotic events were associated with increased activated caspase-3, increased proapoptotic BAX expression, and decreased anti-apoptotic BCL2A1 expression.…”
Section: Trophoblast Cells and Apoptosismentioning
confidence: 99%
“…These apoptotic events were associated with increased activated caspase-3, increased proapoptotic BAX expression, and decreased anti-apoptotic BCL2A1 expression. 55 In pregnant pigs, Cristofolini et al 56 described a 29-fold increase in the apoptosis index (as measured by TUNEL assay) in placental tissue from near-term pregnancies compared to those from mid-gestation.…”
Section: Trophoblast Cells and Apoptosismentioning
confidence: 99%